315 W0180 novel anti-VISTA antibody: Rationale for target patient population and first-in-human trial design in monotherapy and in combination with anti-PD1 antibody. (10th December 2020) - Melero, Ignacio; Gomez-Roca, Carlos; Ferre, Pierre; Ferre, Pierre; Chetaille, Eric; Petain, Aurelie; Thuilliez, Celine; Vandenberghe, Isabelle; Cruzalegui, Francisco; Boudribila, Asmaa; Pavlyuk, Mariya; Marabelle, Aurelien
Abstract : Background: V-domain Ig suppressor of T cell Activation (VISTA) is a negative checkpoint regulator of T cell response. 1 VISTA is expressed within the tumor microenvironment, where its blockade can enhance antitumor immune responses. 2 Furthermore, an increase in VISTA expression has been reported after treatment by anti-PD1/L1 and anti-CTLA4. 3, 4 This confirms that VISTA may play a key role as a mechanism of resistance to the currently used immunotherapies. VISTA/PSGL1 pH-selective biochemical interaction has been recently demonstrated. 5 VISTA and PSGL1 expression pattern, their correlation and their relationship to myeloid infiltrates have been evaluated in samples from patients with solid tumors. K01401-020 (W0180) is a novel anti-VISTA antibody that has the potential to activate T cells when given as a monotherapy 6, and thus to generate added activity when combined with anti-PD1/L1 antibodies in cancer patients. Methods: This phase I/Ib for W0180 consists of 2 parts: an initial dose escalation phase I followed by an expansion cohorts phase Ib. In the dose escalation phase, 2 cohorts of patients will be assessed in parallel: the first cohort will be given W0180 as a single agent and the second cohort will receive W0180 in combination with pembrolizumab. The first dose and the schedule of administration of W0180 in combination with pembrolizumab will be determined using safety and pharmacokinetic data generated in monotherapy. The phase I will allow to determine the Maximum Tolerated Dose and Schedule (MTDS), to characterize Dose-Limiting Toxicities (DLTs) and explore pharmacodynamic activity of W0180 in monotherapy and combination with pembrolizumab. The dose-toxicity relationships will support the dose escalation process and will be used to assess the MTDS and recommended doses for expansion. Following completion of the dose escalation phase, the expansion phase will enroll cohorts of patients with homogeneous tumors to validate the dose/schedule, assess preliminary activity and to explore the potential relationship with VISTA and PSGL1 expression. Results: N/A Conclusions: N/A Trial Registration: N/A Ethics Approval: The study was approved by National French Ethic committee (CPP Ile de France V) and National Spanish Ethic committee (Comité Ético de Investigación Clínica de Navarra) and was registered in the European database (EudraCT: 2019-002299-15). Consent: N/A References: Wang L, Rubinstein R, Lines JL, Wasiuk A, Ahonen C, Guo Y, Lu LF, Gondek D, Wang Y, Fava RA, Fiser A, Almo S, Noelle RJ, VISTA, a novel mouse Ig superfamily ligand that negatively regulates T cell responses. J Exp Med 2011;208 :577–92. Lines JL, Pantazi E, Mak J, Sempere LF, Wang L, O'Connell S, Ceeraz S, Suriawinata AA, Yan S, Ernstoff MS, Noelle R, VISTA is an immune checkpoint molecule for human T cells. Cancer Res 2014;74 :1924–32. Gao J, Ward JF, Pettaway CA, Shi LZ, Subudhi SK, Vence LM, Zhao H, Chen J, Chen H, Efstathiou E, Troncoso P, Allison JP, Logothetis CJ, Wistuba II, Sepulveda MA, Sun J, Wargo J, Blando J, Sharma P, VISTA is an inhibitory immune checkpoint that is increased after ipilimumab therapy in patients with prostate cancer. Nat Med 2017;23 :551–555. Kakavand H, Jackett LA, Menzies AM, Gide TN, Carlino MS, Saw RPM, Thompson JF, Wilmott JS, Long GV, Scolyer RA, Negative immune checkpoint regulation by VISTA: a mechanism of acquired resistance to anti-PD-1 therapy in metastatic melanoma patients. Mod Pathol 2017;30 :1666–1676. Johnston RJ, Su LJ, Pinckney J, Critton D, Boyer E, Krishnakumar A, Corbett M, Rankin AL, Dibella R, Campbell L, Martin GH, Lemar H, Cayton T, Huang RY, Deng X, Nayeem A, Chen H, Ergel B, Rizzo JM, Yamniuk AP, Dutta S, Ngo J, Shorts AO, Ramakrishnan R, Kozhich A, Holloway J, Fang H, Wang YK, Yang Z, Thiam K, Rakestraw G, Rajpal A, Sheppard P, Quigley M, Bahjat KS, Korman AJ, VISTA is an acidic pH-selective ligand for PSGL-1. Nature 2019;574 :565–570 Libon C, Vandenberghe I, Marlin R, Gros W, Leonec M, Gomez-Pacheco M, Gallouet M, Fraboul F, Mahfoudi A, Dereuddre-Bosquet N, Ferré P, K0401-020 anti-VISTA antibody monotherapy increases specific CD8 T cell response in non-human primates. AACR Annual meeting 2020.